2017
DOI: 10.1038/s41598-017-15875-8
|View full text |Cite
|
Sign up to set email alerts
|

Diet selection and n-3 polyunsaturated fatty acid deposition in lambs as affected by restricted time at pasture

Abstract: This study investigates the effects of restricted grazing time on forage selectivity and meat fatty acid deposition of lambs compared to a traditional grazing system. Results showed that the animals preferred to graze pasture species that were more palatable and lower in fibre, while demonstrating a partial preference for species with high protein levels. Leymus chinensis was more preferentially selected by lambs grazing pasture for shorter periods than longer periods. Lambs that grazed for 4 h per day had a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
(41 reference statements)
2
10
0
Order By: Relevance
“…Consequently, n-3 and n-6 PUFA are generated by the Δ-5 and Δ-6 desaturase enzyme, stimulated by n-3 PUFA and a balance of the n-6:n-3 fatty acid ratio (Araya et al, 2004). Similar findings were revealed in the study of Zhang et al, 2017; who found higher C18:3 n-3 contents in broilers fed linseed oil. Moreover, our results presented higher C18:3 n-3 and PUFA levels in breast meat than in thigh meat lipids; as PUFA are preferentially incorporated into phospholipids (Hulan et al, 1988), which are in higher proportions in breast muscles than in thigh muscles (Ratnayake et al, 1989).…”
Section: Efficiency Of Perilla Mealsupporting
confidence: 80%
“…Consequently, n-3 and n-6 PUFA are generated by the Δ-5 and Δ-6 desaturase enzyme, stimulated by n-3 PUFA and a balance of the n-6:n-3 fatty acid ratio (Araya et al, 2004). Similar findings were revealed in the study of Zhang et al, 2017; who found higher C18:3 n-3 contents in broilers fed linseed oil. Moreover, our results presented higher C18:3 n-3 and PUFA levels in breast meat than in thigh meat lipids; as PUFA are preferentially incorporated into phospholipids (Hulan et al, 1988), which are in higher proportions in breast muscles than in thigh muscles (Ratnayake et al, 1989).…”
Section: Efficiency Of Perilla Mealsupporting
confidence: 80%
“…Pasture vegetation is also a source of healthy n3 polyunsaturated fatty acids ( Sun et al., 2012 ; Dal Bosco et al, 2016 ; Michalczuk et al., 2017 ; Zhang et al., 2017 ). Ponte et al.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrently, restricted time at pasture with supplementation improves the growth performance of grazing sheep [ 5 ]. Our previous study found that restricting the grazing of lambs to 4 h per day improved grazing efficiency [ 6 ] and increased health-promoting n -3 unsaturated fatty acids in muscle tissue [ 7 ]. Restricted grazing with supplementation reduced the amount of movement and pasture intake of grazing sheep [ 6 , 7 ], which affected the development of the gastrointestinal tract as well as muscle fiber and carcass quality.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that restricting the grazing of lambs to 4 h per day improved grazing efficiency [ 6 ] and increased health-promoting n -3 unsaturated fatty acids in muscle tissue [ 7 ]. Restricted grazing with supplementation reduced the amount of movement and pasture intake of grazing sheep [ 6 , 7 ], which affected the development of the gastrointestinal tract as well as muscle fiber and carcass quality. The development of the gastrointestinal tract plays a vital role in nutrient digestion and absorption and muscle fibers impact meat quality [ 8 ].…”
Section: Introductionmentioning
confidence: 99%